Investigating the Early Implementation of MFRS136 Disclosure among Top 50 Firms in Malaysia - Abdul Rahman, Aisyah; Mohamed, Ahmad Syubaili; Laili, Nur Hidayah; Khairi, Khairil Faizal (Faculty of Economics and Management, Universiti Kebangsaan Malaysia & Malaysian Accountancy Research and Education Foundation (MAREF), 2017)
The highly prescriptive and technical provisions of MFRS 136 – Impairment of Assets represent a very considerable variation from past practices. This in turn gives increase to questions about the span to which Malaysian businesses and their auditors have fared during the method of transition to a convoluted new reporting regime. Malaysia through Malaysian Accounting Standards Board (MASB) made the requirements of the MFRS 136 - Impairment of Assets mandatory progressively since 1 January 2006 for some or all listed firms in Malaysia. Since then, Malaysian companies are required to comply with the standard. The purpose of this paper is to investigate the compliance level of approved companies on the Bursa Malaysia main market towards the disclosure requirement of MFRS 136 - Impairment of Assets. This study also aims to identifying some factors associated with the level of compliance. The unweighted index was established by constructing the index checklist. The checklist was based on the requirement of disclosure of MFRS 136 (amended in 2009) and the annual reports of 50 sampled firms from 2010 to 2012 were examined. Then, we establish dependent variables and construct econometrical model to test the hypothesis in the research using Estimated Generalized Least Squares (EGLS) weights regression using cross-section weights. The result shows that 28 firms (56%), 27 firms (54%) and 24 firms (48%) out of 50 firms in 2010, 2011 and 2012 respectively failed to comply with requirement of FRS 136 pertaining to goodwill impairment testing. This study suggests that the performance of the top 50 listed companies must improve before Malaysian practice can attain a truly international standard. This study also found that firm size, profitability and auditor type are associated with the extent of compliance with MFRS 136. However, only firm size and profitability were positively associated with the level of compliance meanwhile auditor type were negatively associated with the level of compliance. This indicates that bigger firm and more profitable firms in Malaysia were more motivated to exhibit greater transparency of MFRS 136.